Deskripsi Kesulitan Berbicara Pada Anak Usia 4-5 Tahun di TK Al-Khairat Kota Gorontalo - Fitriyah Ningsi R. Bakari; Pupung puspa Ardini; Rapi Us. Djuko (Inovasi Pendidikan dan Anak Usia Dini, 2024)
This study aims to desribe speech difficulties n children aged 4-5 years at TK Al-Khairat Kindergarten, Gorontalo City. The researcher employed a qualitative research method focusing on the speech diffuculties experienced by children. The study subjects were three children and their parents at TK Al-Khairat Kindergarten in Gorontalo City, Data was collected through interviews and documentation. Data analysis was conducted through data reducation, data ranging from poor arculation to difficulties in understanding and using vocabulary. The causes influencing these difficulties include motor speech disorders such as apraxia, lack of supportive social interactions, and familly communication patterns. These speech difficulties significantly impact the children’s social-emosional development, such as low self-concept and difficulties building social-emotional development, such as low self-concept and difficulties building social relationship. The study highlights the importance of early detection and appropriate intervention to help children overcome speech difficulties, ultimately supporting their social, emotional, and academic development.